Effect of an activated carbon filter on the microbial quality of water. - Fiore, J V (1977)
Recently, there has been growing concern that microbial health hazards can be increased by the use of activated carbon filters in domestic water systems. The present study was undertaken to investigate the effect of carbon filters on the microbial content of water. Results indicated that the microbial content of filtered and unfiltered water increased to about the same level on overnight standing and, in both cases, was reduced by flushing the next day. In addition, the use of activated carbon for the filtration of contaminated well water over a period of 11 weeks had no effect on the total or coliform count. Under use conditions, activated carbon filters were found to have no significant effect on the number of bacteria present in the water.